Pengaruh Variasi Berat Filler Black Karbon Aktif Kulit Bambu Terhadap Struktur Dan Kekuatan Tarik Komposit Polyester - Tri Mulyanto, Wahyu; , Ir. Ngafwan, MT (2016)
ABSTRACT This study aimed at describing the influence of micro and nano bamboo shell activated carbon as a filler on the mechanical and physical properties of polyester composites. Manufacture of composites using a variation filler weight fraction of micro and nano activated carbon of 0.05 grams, 0.1 grams, 0.15 grams, 0.46 grams and 0.92 grams of the polyester resin Yukalac 157 BQTN - EX. Mixing carbon particles with resin using a stirring with a maximum rotation speed of 2200 rpm for 15 minutes. Making test specimen using a standard tensile pull test ASTM D 638-01. Prior to tensile testing, the specimen was photographed a macro to determine the composition of the carbon particles in the composite. The results of the macro image obtained value - average distance and diameter of the carbon particles in the specimen KA 0.05 grams of 17.50 μm, KA 0.1 gram of 16.05 μm, KA 0.15 grams of 15.68 μm, KA 0 , 46 grams of 15.44 μm, and KA 0.92 grams of 14.82 lm. Tensile test results obtained tensile strength (yield) on a specimen of 0.05 grams of 30.65 N / mm2. While the value of the highest maximum strain on specimens KA 0.05 gram by 1.57%, At the time of the length occurs diminution in the cross-section area of the gauge, then led Tensile Strength and Strain Drag increases as the reduced amount of carbon filler in composites. SEM (Scanning Microscope Electrone) made after the tensile test specimens, SEM is because the object is part of the fault on tensile test specimens to determine the structure of the material on the fracture, SEM analysis using 1500x magnification. Based on the SEM images, it can be observed the value of the volume fraction of carbon. The average value obtained volume fraction of activated carbon to the weight fraction of 0.05 grams of 14.74%, the weight fraction of 0.1 grams of 16.85%, 0.15 gram weight fractions of 17.94%, the weight fraction 0, 46 grams of 20.5%, and the weight fraction of 0.92 grams of 27.01%. Keywords: Filler, bamboo skin Carbon, Activated Carbon, Carbon Black